Interpretive structural modeling of physician-patient communication avoidance - Rohollah Mirjalili; Hossein Kazemi; Malikeh Beheshtifar (Shahid Beheshti University of Medical Sciences, 2023)
Background: Communication between physician and patient and medical personnel is the cornerstone of good medical care and communication skills play an important role in patient satisfaction and their treatment. The purpose of this research was to model the interpretive structure of avoiding communication between physicians in the public hospitals of Yazd city. Methods: This research was conducted qualitatively and with a structural interpretative method in two hospitals of Shahid Sadougi University of Medical Sciences, Yazd. The study samples included 12 general practitioners and specialists working in the hospital, who were selected as a sample in a purposeful way until the theoretical saturation limit was reached. Data were collected using semi-structured interviews. Results: Interpretive structural modeling showed that religious and belief factors were the cornerstones of the model. Hospital environment factors, challenges related to the medical profession, challenges related to colleagues, challenges related to the patient, information disorder, lack of skills, and social harms are on the second level, which affect the first level factors. First-level family factors and psychological factors by themselves do not affect other factors. Conclusion: The ability to communicate correctly was one of the most important characteristics of health workers, and communicating correctly has positive effects on patients. Disruption in communication leads to misdiagnosis, reducing patient participation in treatment, and physician-patient communication is effective in providing primary health services and the efficiency of medical services.